Pengembangan Modul Pembelajaran Teknik Kerja Bengkel sebagai Bahan Ajar Kelas X Teknik Audio Video - Widada, Fariz Budi; Waluyanti, Sri (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
The 2013 curriculum encourages the development of instructional media that can encourage the creation of more effective learning and support students to be creative. This research aims to determine the steps to develop a workshop technique module for learning and satisfying process for learning. This learning module is used in workshop technique, subject class X skill competency audio-video technique in SMK Muhammadiyah 3 Yogyakarta. This research using method Research and Development (R&D) version Borg and Gallyang have been simplified by Anik Ghufron with 4 steps: 1) introduction study; 2) Development; 3) experiment test; 4) disseminate. The result of the research shows from the validation material expertise has score 3,40 and claimed very satisfy, validation for media expertise has score 3,75 and claimed very satisfy. Meanwhile, the result for experiment  test  get  score 3,20  and  claimed  to  satisfy.  Consideration  from validation  result  and experiment test, thus learning module is developed satisfy for used on process workshop technique learning